Effect of filler surface treatment on the properties of recycled high‐density polyethylene/(natural rubber)/(Kenaf powder) biocomposites. Issue 4 (27th May 2014) - Cao, Xuan Viet; Ismail, Hanafi; Rashid, Azura A.; Takeichi, Tsutomu; Vo‐Huu, Thao
<x xml:space="preserve">Abstract</x> Biocomposites were prepared from a kenaf core powder and recycled high‐density polyethylene/(natural rubber) blend by using an internal mixer at 165oC and 50 rpm. The effect of the filler content and the filler surface treatment was studied. Chemical modification of kenaf filler was performed with alkali pretreatment followed by treatment with silane. Scanning electron microscopy and infrared spectroscopy studies confirmed changes in the chemical compositions and structural characteristics induced through the modification. It was found that treated biocomposites offered higher tensile strength and tensile modulus, but lower elongation at break compared with untreated biocomposites. Lower water absorption and higher thermal stability of the resultant biocomposites were also obtained when treated fillers were used. J. VINYL ADDIT. TECHNOL., 20:218–224, 2014. © 2014 Society of Plastics Engineers